I sistemi di risoluzione stragiudiziale delle controversie in materia bancaria e finanziaria - Cannavo, Mauro (Università di Pisa, 2012)
Il presente elaborato mira ad analizzare le forme di tutela accordate in sede europea al “consumatore” si servizi finanziari, al fine di verificarne, da un lato, l’adeguatezza rispetto all’evoluzione normativa che ha interessato tale segmento del mercato (Capitolo I) e, dall’altro lato, le modalità e le tecniche di diffusione nell’ordinamento italiano (Capitolo II) e in quelli dei principali Paesi Europei (Capitolo III). L’indagine muove dal processo di integrazione comunitaria avviato nel 1999 con l’elaborazione del “Financial Service Action Plan”, mettendo in luce come tale azione stia progressivamente contribuendo, attraverso la predisposizione di nuove regole e principi, alla creazione di un “diritto privato europeo”. In tale contesto, infatti, lo spazio rappresentato dal mercato dei servizi finanziari è significativo e di eccezionale rilevanza. Si è osservato, infatti, come l’integrazione dei mercati finanziari – avviata dalle Istituzioni europee, tra l’altro, attraverso l’aggiornamento della normativa comunitaria sui servizi di investimento (direttiva MiFID) – abbia avviato, e progressivamente sostenga, la massima armonizzazione delle regole economiche e giuridiche applicabili alle relazioni con i clienti, anche attraverso l’introduzione di nuovi meccanismi di tutela dei consumatori, volti a preservare la parte “debole” del rapporto contrattuale dai fisiologici rischi connessi alla prestazione dei servizi finanziari. In tale contesto, si è evidenziato come l’omogeneizzazione delle regole dei mercati finanziari abbia comportato, da un lato, l’aumento del flusso di risparmio destinato agli investimenti cross-border, nonché il progressivo coinvolgimento dei consumatori nelle transazioni finanziarie ma, dall’altro lato, abbia contribuito ad esporre maggiormente gli stessi ai rischi connessi agli eventi di crisi che hanno interessato le economie a capitalismo avanzato (ad esempio, il default della banca d’affari Lehman Brother’s). L’esposizione della clientela a situazioni di instabilità, peraltro, è fortemente avvertita anche sul versante dei servizi bancari tradizionali, non soltanto in ragione della diffusione del modello di banca universale e multicanale, ma che per effetto dell’attesa internazionalizzazione dei player del mercato, conseguente al livellamento del relativo “campo da gioco”. Si è perciò sottolineato come la proliferazione delle controversie intermediario-cliente nei diversi segmenti del comparto bancario-finanziario abbia mostrato come il nuovo sistema di tutele introdotto dal legislatore comunitario non sia stato in grado, da solo, di garantire la massima protezione dei consumatori dai rischi connessi alla fruizione dei servizi finanziari. A tale proposito, ci si è interrogati – anche alla luce della copiosa letteratura nazionale ed europea in materia – riguardo ai rimedi esperibili per superare le criticità legate alle procedure giudiziali di risoluzione delle controversie transfrontaliere (i.e. la durata dei tempi processuali, ovvero il costo per accedere alla giustizia), giungendo ad individuare nei sistemi alternativi di risoluzione delle controversie (c.d. ADR) una valida alternativa rispetto alla tutela giudiziale ordinaria. Ancora nel corso del Capitolo I, si è dato conto di come tali meccanismi di mediazione e conciliazione – caldeggiati e, in parte, disciplinati dalle istituzioni comunitarie – potranno, da un lato, comportare la semplificazione e la deburocratizzazione degli apparati giudiziari e, dall’altro, offrire un ulteriore presidio di tutela per i cittadini europei, particolarmente esposti ai rischi connessi ad attività complesse come la prestazione dei servizi di investimento. Come evidenziato nel corso del Capitolo II, non sorprende che in un settore fisiologicamente esposto al rischio di contenzioso come il comparto dei servizi finanziari, le Istituzioni comunitarie abbiano introdotto e progressivamente sospinto la diffusione in Europa dei modelli di ADR, appunto come strumenti di risoluzione delle controversie alternativi agli ordinari rimedi di natura giudiziaria. E sulla spinta comunitaria, anche il legislatore italiano sta progressivamente introducendo nel nostro ordinamento nuove modalità e nuovi sistemi per la risoluzione stragiudiziale delle controversie insorte in sede di prestazione dei servizi finanziari: tra le prime, la disciplina della mediazione finalizzata alla conciliazione delle controversie in materia civile e commerciale (di cui al d.lgs. 4 marzo 2010, n. 28); tra i secondi, i due nuovi organismi di derivazione pubblica, rappresentati dall’Arbitro Bancario Finanziario attivo presso la Banca d’Italia e la Camera di Conciliazione e Arbitrato, costituita presso la Consob. Si è visto, quindi, che le esigenze di tutela della clientela hanno condotto negli ultimi anni all’emanazione di regole e principi, come la disciplina della trasparenza del 2003 (successivamente novellata nel 2009 e, da ultimo, nel 2011 per recepire le nuove regole in materia di contratti di credito ai consumatori) e le regole di funzionamento dei sistemi di risoluzione stragiudiziale delle controversie, che operano proprio a completamento del quadro delle iniziative di tutela della clientela bancaria e finanziaria, come strumenti di redress rapidi, economici ed efficaci. Sempre nel corso del Capitolo II, quindi, si analizzano le caratteristiche principali dell’organismo nazionale deputato alla risoluzione stragiudiziale delle controversie bancarie, costituito dall’Arbitro Bancario Finanziario, al fine di rappresentare la natura giuridica di tale meccanismo, il relativo ambito di applicazione territoriale ed oggettivo, nonché individuando i rimedi esperibili dagli intermediari avverso le decisioni pronunciate dall’ABF. L’indagine prosegue attraverso l’indicazione degli elementi essenziali della Camera di Conciliazione e Arbitrato, istituita presso la Consob al fine di redimere le controversie insorte in sede di prestazione dei servizi di investimento, anche attraverso un approfondito confronto con la natura giuridica e l’ambito di applicazione dell’ABF. Infine, nel Capitolo III dell’elaborato – dopo aver esaminato le principali ragioni poste alla base della diffusione degli strumenti ADR in Europa, le principali iniziative legislative (direttiva mediation) e di autoregolamentazione (reti EEJ-NET e FIN-NET) in materia – si offre un’analisi dei principali sistemi ADR attivi in Europa, attraverso una dettagliata indagine comparatistica che ha interessato gli ordinamenti francese, spagnolo, tedesco e inglese. La menzionata indagine, in particolare, ha messo in luce le principali differenze e le numerose analogie presenti tra i sistemi ADR attivi nell’Unione europea, principalmente con riguardo alla natura giuridica dei rispettivi organismi, alle funzioni svolte, alle condizioni di accesso ai sistemi, nonché alle caratteristiche delle relative decisioni.
Keywords: ABF; ADR; Arbitrage; Arbitragem; Arbitration; Arbitrato; Arbitro; Banca; Cliente; Collegio; Conciliazione; Consob; Controversie; Finanziario; Intermediari; Intermediazione; MARD; Mediación; Mediation; Mediazione; Mediação; Médiation; Reclamo; Ricorso; Stragiudiziale

L'émergence du droit international des investissements : contribution des traités bilatéraux d’investissement et de la jurisprudence du CIRDI - Danic, Olivia (Université Paris 10, 2012)
La relation dialectique qui unit les traités bilatéraux d’investissement et la jurisprudence du Centre International de Règlement des Différends relatifs aux Investissements (CIRDI) a fait émerger un droit international des investissements. La rencontre de ces deux dynamiques a permis de dépasser leur caractère a priori isolé et fragmenté, pour aboutir à un véritable système juridique international, doté d’une structure, d’une logique et de principes propres. En effet, rien ne pouvait laisser envisager une telle évolution, le régime de l’investissement international se fondant sur une multitude de traités bilatéraux et sur une instance arbitrale ne faisant qu’héberger des tribunaux éphémères. Les mouvements de va-et-vient qui unissaient ces deux phénomènes ont permis de lui donner des normes quasi-universelles, mais aussi un véritable juge à la compétence extensive et surtout de lui insuffler l’unité, l’efficacité, la cohérence et la complétude, faisant de plus en plus ressembler le droit international des investissements à un véritable ordre juridique qui, même s’il relève du droit international, lui permet également d’évoluer. The relashionship between bilateral investment treaties and the case-law of the International Centre for Settlement of Investment Disputes (ICSID) has led to the emergence of international investment law. It seems surprising, at first, that these two distinct phenomena, being isolated and fragmented, would reach a certain degree of unity so that a real international legal order could appear, with its own structure, reasoning and principles. No one could foresee such an evolution, the regime of international investment being founded on a large number of bilateral treaties and on an international institution which only provides facilities for arbitration of international investment disputes. The unity of the system has been discovered through the back and forth movements between treaties and arbitration which gave rise to international investment law. This system has now almost universal norms, an international judge and satisfies the criteria of unity, efficiency, consistency and completeness, producing a real legal order functioning in accordance with its own logic. There is no doubt that this evolution will influence the course of international law.
Keywords: Arbitrage; Arbitrage (droit); Arbitration; Bilateral Investment Treaties (BITs); CIRDI; Centre international pour le réglement des différends relatifs aux investissements; Droit international; ICSID; International law; Investissements; Investissements étrangers (droit international); Investment; Investments; Jurisprudence; Legal order; Ordre juridique; Traité bilatéral d’investissement

La responsabilité sociétale des entreprises et la médiation - Mattei, Laetitia (Université Paris 9, 2012)
Les crises actuelles, sous leurs multiples aspects, mettent en lumière la responsabilité des entreprises dans notre société, bousculant ainsi l'un des dogmes néolibéraux résumé par la célèbre formule de Milton Friedman (1970) : « La responsabilité sociétale de l’entreprise est d’accroître ses profits». C’est en réaction à ces crises et grâce au rôle actif de la société civile qui condamne désormais certaines pratiques, que le concept de responsabilité sociétale des entreprises (ci-après RSE) a émergé. L’enjeu est donc, aujourd’hui, de mettre en place un marché responsable entre l’entreprise et ses parties prenantes. Le législateur, par la loi Grenelle I, dispose que la médiation sera un des outils de mise en oeuvre de la RSE. Il en appelle donc au développement du droit processuel qu’est la médiation pour mettre en oeuvre ce droit substantiel qu’est la RSE. La médiation, à la fois préventive et curative, est donc un outil de mise en oeuvre de la RSE. Le couple RSE et médiation permet ainsi de combiner efficacité économique, respect social,sociétal et environnemental
Keywords: Company; Entreprise; Grenelle Environnement 2007; Législation; MARD; Mediación; Mediation; Mediação; Médiation; Paris; Parties prenantes; Parties prenantes (gestion d'entreprise) -- France; Procédure (droit); Responsabilité; Responsabilité sociétale; Responsibility; Sociétal; Stakeholders

The Influence of ICC Arbitral Decisions on Canadian Law: Comparative Study between Civil Law and Common Law Jurisdictions - Hedaraly, Saleha (Université de Montréal, 2012)
L’objectif de cette recherche est de démontrer que les décisions arbitrales de la Chambre de commerce internationale peuvent être considérées comme une source potentielle de droit au Canada. Il existe actuellement une incertitude quant au droit matériel utilisé en arbitrage international pour résoudre les différends commerciaux. Bien que l’utilisation de la lex mercatoria pour résoudre un litige soit une option, elle se heurte à de nombreuses incertitudes terminologiques et conceptuelles. L’utilisation d’une approche méthodologique de la lex mercatoria permettrait une classification de ses sources en deux branches: (1) le droit statutaire international et (2) le stare decisis des tribunaux d’arbitrage commercial international. Une telle approche méthodologique conférerait plus de certitude quant à l’application d’un droit uniforme. De plus, elle faciliterait l’étude de l’interlégalité entre les règles de la lex mercatoria et le droit matériel interne. Plus particulièrement, elle permet de comparer les similitudes et les différences des règles du droit matériel entre les décisions arbitrales internationales, le droit statutaire international et les juridictions canadiennes de common law et de droit civil. Cette comparaison rend possible une évaluation de l’influence potentielle des décisions arbitrales de la Chambre de commerce internationale sur le droit matériel canadien et si cette influence est plus importante en droit civil ou en common law. This paper’s objective is to demonstrate that the International Chamber of Commerce’s arbitral awards may be considered as a potential source of law in Canada. There currently exists an uncertainty as to the substantive law used in international commercial arbitration. While the use of lex mercatoria to solve commercial disputes is often referred to, several terminological and conceptual uncertainties undermine its credibility. The use of a methodological approach to lex mercatoria allows for a twofold classification of its sources through: (1) international legislation and (2) stare decisis from international arbitral tribunals. This methodological approach provides a greater certainty for the application of a uniform law which, in turn, allows for the study of interlegality between rules of lex mercatoria and substantive domestic law. Furthermore, this methodological approach facilitates the demonstration of the similarities and differences between international arbitral decisions, international legislation as well as Canadian common law and civil law jurisdictions. This comparative analysis will allow the study of the potential influence of the arbitral decisions of the International Chamber of Commerce on substantive Canadian law and whether this influence is more important in civil law or common law.
Keywords: Approche méthodologique; Arbitrage; Arbitragem; Arbitral decisions; Arbitration; CCI; Civil law; Common law; Droit civil; Droit commercial transnational; Décisions arbitrales; ICC; Interlegality; Interlégalité; Lex mercatoria; Methodological approach; Sentences arbitrales; Transnational commercial law

The legal and institutional framework for the enforcement of online consumer arbitration awards: evidence from Australia and Sri Lanka - Kananke, Chinthaka Liyanage (La Trobe University, 2012)
Keywords: Australia; Commercial law; Conflict of laws; Consumer protection; Dispute resolution; Electronic commerce; Sri Lanka

A proposal to guide future draft article provisions for a model harmonised international commercial arbitration law code (HICALC) in the Middle East and North Africa or a uniform Arab arbitration law - Ayad, Mary Boulos (Macquarie University, 2012)
MENA law codes are a well-crafted blend of civil and Islamic law in which civil law principles do not contravene with Islamic provisions. They were originally based on Sanhuri’s codes to varying degrees. Yet, common law principles derived either from English common law or Islamic customary usages are unidentified and thus ignored. Here, this lacuna is rectified through a comparative analysis of the primary data (eg, cases, statutes and arbitral award decisions), adding common law and uncodified Islamic custom to MENA law codes. The purpose of this comparative analysis is to allow common legal principles found at civil, common and Islamic law to be distilled in the service of creating a new harmonised international commercial arbitration law code (HICALC) or uniform Arab arbitration law (UAAL) for adoption in the MENA.1 These principles already form part or all of the legal systems in the MENA. They can be readily assimilated into a harmonised or uniform code. Would this new harmonised code lead to higher arbitral award enforcement in the MENA? According to the evidence the answer is yes. The author understands that at the present time the HICALC articles are ambitious and as such they are a beginning point and can initially be taken as a harmonised international commercial arbitration common rule (HICACR). A brief overview of the history of harmonisation is given. An assessment of the status of the laws and traditions of the MENA was carried out. A comparative analysis of the relevant differences and similarities of the case study countries (Egypt and the United Arab Emirates) was carried out to show the gaps in the laws and areas requiring reform. An analysis of enforcement of arbitral awards was carried out. The unique problems that ICA and IIA encounter in the MENA as derived from an analysis of cases and the laws therein are expounded in consideration of matters pertaining to enforcement. A comparative analysis of universal principles which must be included in a new code, including custom, was carried out. An analysis of the unique features and unique needs of the MENA was carried out in order to inform the Draft Article Provisions. An analysis of important international legal instruments dealing specifically with international arbitration and the gaps therein is given. The draft articles for a HICALC or uniform Arab arbitration law were derived as a result of these multiple layers of analysis. The matters of compétence de la compétence, expropriation, interest, public policy and sovereign immunity are highlighted as the most important areas requiring urgent reform. The results of this research are suggested Draft Article Provisions for a model Harmonised International Commercial Arbitration Law Code (HICALC) or a uniform Arab arbitration law. Future drafters may refer to and revise these articles for implementation. The synthesis of theory and practice addresses doctrinal matters that arise in international investment arbitrations and international commercial arbitration, with a focus on investor–State arbitrations. This synthesis provides a new theoretical conception of the jurisprudence of international arbitration, particularly in regard to the matters of res iudicata, precedent and expansion of arbitral tribunal powers and jurisdiction.
Keywords: Arab countries; Arbitrage; Arbitragem; Arbitration; Arbitration Law; Arbitration and award; Commercial law; Commercial law (Islamic law); Common rule; Dispute resolution; HICACR; HICALC; Harmonised International Commercial Arbitration; International commercial arbitration; MENA law codes; Middle East; North Africa; UAAL; Uniform Arab arbitration law

L'Influence de l'accueil de la sentence arbitrale par le juge algérien sur l'efficacité de l'arbitrage commercial international - Hocine, Farida (Université Mouloud Mammeri, 2012)
Keywords: Algérie; Arbitrage commercial; Arbitrage international; Arbitragem; Arbitraje; Arbitration; Efficacité de l'arbitrage; Juge algérien; Sentence arbitrale

From Port Louis to Panama and Washington DC: Two Regional Approaches to International Commercial Arbitration - Bashi Rudahindwa, Jonathan (European Journal of Law Reform, 2012)
In recent decades, regional efforts have been made to reform and harmonize the rules governing international arbitration. These efforts have resulted in the adoption of regional instruments governing commercial arbitration in specific areas. This paper analyzes the arbitration regimes created at a regional level in Africa and America, and particularly focuses on arbitral institutions that were created within the Organization for Harmonization of Business Law in Africa (OHADA) and within the Organization of American States (OAS). The objective of the paper is to identify any advantages provided by either regime, which can help improve regional and international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial Arbitration

Efetividade das estipulações voltadas à instituição dos meios multiportas de solução de litígios - Guerrero, Luis Fernando (Universidade de São Paulo, 2012)
Este estudo examina as estipulações voltadas à instituição de meios multiportas de solução de controvérsias, mecanismo responsável por materializar a vontade da partes em solucionar os seus conflitos via métodos alternativos ou adequados de solução de controvérsias, tendo relevante papel na materialização do escopo social do processo. Há uma clara dicotomia entre os denominados métodos de solução de controvérsias consensuais, nos quais a própria participação das partes levará à solução e à conformação do litígio e, de outro lado, os métodos adjudicatórios de solução de controvérsias, no qual haverá um terceiro imparcial escolhido pelas partes ou de acordo com mecanismos por elas estabelecido e que será responsável pela solução da controvérsia. Existem ainda métodos combinados ou mistos, em que são aglutinados elementos dos métodos denominados primários, quais sejam negociação, conciliação, mediação e arbitragem. Clara a diferença entre essas categorias de métodos de solução de controvérsias, deve-se analisar, ainda, se há alguma diferença no tocante à vinculação das partes a cada uma das mencionadas categorias de solução de controvérsias e, com grande importância, de que modo métodos consensuais podem interferir no surgimento e desenvolvimento de métodos adjudicatórios. Em relação à vinculação dos métodos de solução de controvérsias adjudicatórios, a grande referência no direito brasileiro é a arbitragem, que conta com legislação própria e deve muito de seu sucesso no atual estado dos métodos de solução de controvérsias no direito brasileiro a alterações relativas à sua vinculação e efetivação. Nitidamente, há uma inserção das cláusulas de solução de controvérsias, seja qual for o método utilizado no âmbito da ciência processual. A base de tais cláusulas é de direito privado, fundamentando-se em institutos bastante conhecidos: transação e compromisso que ganharam a categorização jurídica de contrato após o Código Civil de 2002. Do ponto de vista da adoção desses instrumentos jurídicos como veículos da utilização dos métodos de solução de controvérsias, são previstas técnicas diversas de uso. A primeira é extrajudicial, baseada na planificação de solução de conflitos, que pode ser feita pelas partes e seus advogados, e uma segunda, que é extrajudicial baseada no caseflow e no case management, nos quais o Judiciário assume o papel de coordenador e aplicador de tais métodos. A relação entre os métodos de solução de controvérsias ganha caráter dinâmico na medida em que determinados sistemas de solução de controvérsias são combinados para uma dada questão. Trata-se das chamadas cláusulas escalonadas que têm por escopo acompanhar a escalada de litigiosidade que possa surgir em determinada discussão jurídica, combinando métodos consensuais e adjudicatórios de solução de litígios. Em qualquer situação, de acordo com os termos dos arts. 158 e 466-B do Código de Processo Civil que podem analogamente ser comparados com os arts. 4.º e 7.º da Lei de Arbitragem, há a total vinculação das partes ao método de solução de controvérsias escolhido. Questão bastante tormentosa é a inserção e a inter-relação dos métodos de solução de controvérsias, especialmente com o processo civil e os efeitos que daí podem decorrer. Nesse aspecto, sendo um método consensual, as partes que a ele aderiram terá que realizá-lo antes da busca de um método adjudicatório de adesão voluntária, como é a arbitragem, ou um método adjudicatório inevitável, como é o Judiciário. Trata-se do efeito negativo das cláusulas ADR. Contudo, há que verificar que efeitos seriam gerados aos métodos adjudicatórios pela não realização de um método consensual precedente. Os métodos de solução de controvérsias poderiam ser encarados como pressupostos processuais, condições da ação ou questões prévias, promovendo diferentes resultados em um processo judicial ou arbitral. Há que se buscar a solução que melhor se adequar a um contexto de solução de controvérsias. Desta feita, os MASCs devem ser colocados como hipóteses suspensão dos processos arbitral ou judicial, suspensão essa que deve durar até a realização do referido método acordado anteriormente, garantindo-se a sua eficácia. No tocante a este ponto, o Estado tem um relevante papel político e legislativo de modo a incentivar a utilização de tais métodos e garantir-lhes a eficácia. Além disso, a parte que se furtar está sujeita a consequências contratuais que podem ser previstas, tais como a imposição de multas e cláusulas penais. Vislumbram-se também hipóteses de perda de uma chance, com o agravamento do litígio e prejuízos que podem advir do tolhimento da chance de um método de solução de controvérsias produzir um resultado. De qualquer modo, aquele que pretendia utilizar o método, para se valer dessas possíveis indenizações, tem o dever de mitigar o próprio dano como resultado da mesma cláusula geral de boa-fé que, ao reverso, obrigou o ex-adverso a utilizar o método e foi violada. Pode-se pensar nesse contexto, ainda, a possibilidade de métodos alternativos de solução de controvérsias serem estabelecidos por meio de cláusulas que prevejam a venda de excussão entre as partes ou mesmo medidas corporativas, tais como ocorrem na BM&F Bovespa, apenas de acordo com a manifestação de vontade das partes de adesão ao referido sistema, sendo uma prova da força e extensão do vínculo surgido de uma estipulação de solução de controvérsias, ainda que consensual. Há, de qualquer modo, uma execução por transformação em que a manifestação de vontade apresentada pelas partes pode ser efetivada pelo magistrado permitindo a utilização dos métodos de solução de controvérsias a partir do momento em que ocorreu a adesão das partes. Por fim, a confidencialidade que pode ser aplicada aos métodos de solução de controvérsias tem natureza contratual, não interferindo na eficácia das cláusulas ADR. This study examines the stipulations aimed to establishing alternative settled mechanism responsible for materializing the will of the parties to resolve their disputes through alternative or appropriate dispute settlement with a relevant role in the materialization of the social scope of the process. There is a clear dichotomy between the called consensual methods of dispute resolution in which the participation of the parties will lead to the solution and the conformation of the dispute and, on the other hand, the called adjudicatory methods in which an impartial third party will be chosen by parties or in accordance with mechanisms established by them and will be responsible for resolving the dispute. There are also mixed or combined methods, which contains elements of the primary methods, namely, negotiation, conciliation, mediation and arbitration. Differences between these categories of methods of dispute settlement shall be analyzed, even if there is any difference with respect the binding feature of those methods and, with great importance, so that consensual methods can interfere in the emergence and development of adjudicatory methods. In relation to binding adjudicatory methods of dispute settlement, the most important reference in Brazil is Arbitration. Its Law is responsible for it succed as a method of dispute resolution in the Brazil, specially for ten. changes to their binding feature and enforcement of its result, now recognized as a sentence. The legal basis of such clauses is private law and are based on well-known institutions: transaction and commitment that are a contractual legal categorie after the Civil Code. From the standpoint of using, these legal instruments are vehicles and are expected to use different techniques. The first rendition is based on planning for conflict resolution that can be made by the parties and their lawyers and a second which is based on caseflow and case management, in which the judiciary takes over the role to coordinate and implement these methods. The relationship between the methods of dispute settlement became dynamic when individual methods of dispute settlement are combined to a given question. These are the called staggered terms which seeks to track the escalation of litigation that may arise in a particular legal issue, combining both consensual and adjudicatory dispute resolution methods. In any event, in accordance with the terms of the arts. 158 and 466-B of the Civil Procedure Code that can similarly be compared with the arts. 4o and 7o of the Arbitration Act, there is the share of binding feature of the method of dispute resolution chosen. Question very stormy is the interrelationship of the insertion of dispute resolution methods, especially consensual and adjudicatory methodse. In this aspect, a method is agreed, the parties have to do it before the search for an adjudicatory method. This is the negative effect of ADR clauses. However, there it is found that the effects would be generated by methods Adjudicative not performing a method consesual precedent. The methods of dispute settlement may be seen as procedural requisites, conditions of action or issues prior action by promoting different results in a lawsuit or arbitration. We must seek the solution that best fits the context of a multi door dispute settlement. The conclusion is that the ADR methods should be placed as hypotheses of suspension for arbitration or judicial processes. That suspension should last until the completion of this method previously agreed, assuring its effectiveness. Concerning this point, the State has an important political and legislative role in order to encourage the use of such methods and guarantee their effectiveness. In addition, the part that is subject to evade contractual consequences that can be provided such as the imposition of fines and penalty clauses. In case of ADR clauses breach the lost of a chance theory shall applyo, with increased litigation and damages that may arise from the chance of stunting a method of dispute resolution to produce a result. Anyway, who intended to use the breach of the other party to take advantage of possible damages, has the duty to mitigate the loss itself as a result of the same general clause on good faith that, in reverse, enforces the former adverse to using the method and was violated. One might think in this context also the possibility of alternative methods of dispute settlement be established by means of clauses providing for the sale of excussion between the parties or even intracorporis issues such as occur in the BM&F Bovespa, only in accordance with the manifestation the will of the parties to accede to such a system, a testament to the strength and extent of the relationship arising from a stipulation of settlement of disputes, even if consensual. The intetion to use an alternative dispute resolution shall be given by the partíreis but in case of breach of this obligation the interested party can obtain an mandatory decision by the Judge indicating that the other party must attend the dispute resolution method. Finally, the confidentiality that can be applied to methods of dispute settlement is contractual in nature, not interfering with the enforcement of ADR clauses.
Keywords: ADR; Civil Procedure; Conciliação (processo civil); Direito processual civil; Dispute Resolution; Enforceability; Multidoor; Solução de conflito; Transação; Tutela jurisdicional

Arbitrability in the context of Ghana's new arbitration law. - Mante, Joseph; Ndekugri, Issaka (International arbitration law review, 2012)
Examines the approach of Ghana's Alternative Dispute Resolution Act 2010 to the question of arbitrability. Reflects on the concept of arbitrability under international law, the relevant trends emerging from case law, and the approach adopted by the Ghanaian High Court in Attorney General v Balkan Energy LLC. Reviews the Act's arbitrability exemptions, their implications for international arbitration in Ghana, the potential jurisdictional challenges under the legislation and how its provisions could be amended to increase its conformity with international trends on arbitrability.
Keywords: Arbitrability; Arbitrage; Arbitragem; Arbitration; Comparative law; Ghana; International commercial arbitration; Jurisdiction

Reflections on finality in arbitration - Roodt, Christa (De Jure, 2012)
Ondersoek na die Finaliteit van 'n Arbitrasiebevel Hierdie artikel oorweeg die Telcordia- en Lufuno-sake vanuit die oogpunt van die finaliteit van 'n arbitrasiebevel. Die vraag wat te berde kom, is wanneer 'n arbitrasiebevel finaliteit bereik waar 'n saak voor meer as een forum (arbitrasie en staatlike howe), in meer as een jurisdiksie gevoer word. Die prosedurele meganismes wat Amerikaanse en Suid-Afrikaanse howe tydens die Telcordia-dispuut toegepas het asook hul onderskeie benaderings tot res iudicata, het 'n groot mate van ooreenstemming getoon. Dit is te verstane dat die afhandeling van 'n internasionale proses vertraag kan word deur bepaalde grondwetlike regte wat die spoed van die afhandeling van 'n saak kan beïnvloed. Nietemin, indien die reg op 'n billike verhoor op enige stadium in die verrigtinge gepleit mag word, word 'n geleentheid geskep vir die dispuut om vryelik te eskaleer gedurende die verhoor. Dit kan die hofproses oopstel vir misbruik en die afhandeling van die geskil vertraag. Die minderheidsbeslissing in Lufuno skenk 'n mate van oorweging aan die potensiële negatiewe implikasies hiervan. Die finaliteit van die geskilbeslegtingsproses kan na behore bestuur word aan die hand van 'n wyer interpretasie van res iudicata in internasionale dispute en 'n meer geredelike ondersoek hierna, op die hof se inisiatief. Die moontlikheid dat die Telcordia-dispuut verder bespoedig sou kon word, word ondersoek met verwysing na die New York Konvensie op die Erkenning en Afdwing van Arbitrasiebevele van 1958, en aan die hand van aanbevelings wat deur ander gerekende internasionale liggame uitgereik is.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration

Lex mercatoria in international arbitration theory and practice. Vol 1 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Lex mercatoria in international arbitration theory and practice. Vol 2 - Elcin, Mert (European University Institute, 2012)
This dissertation suggests a new theory of lex mercatoria that takes into account the complex and spontaneous order of international commerce. Since the emphasis is put on the nature of this order, the concept of lex mercatoria is examined as an ex post governance mechanism resolving contractual disputes with a view to maintaining and restoring the order of international commerce, without focusing on the traditional distinction of the doctrine between national and non-national legal rules applicable to the substance of such disputes in explaining the concept. The aim is to reflect lex mercatoria’s subtle effect on the practice of international arbitration, and to provide an explanation of lex mercatoria as a solution to the problems of the institution of international arbitration in terms of uncertainty and unpredictability of awards, rather than representing it as a factor aggravating those problems. Lex mercatoria is defined as the law of adjudication of the disputes arising from international commercial contracts on the basis of a few substantive and procedural principles, under which the reasonable expectations of the parties to a particular contract become the single source of their contractual rights, obligations and risk allocations. The argument is that lex mercatoria can be applied to both the choice of law analyses and the substance of the disputes in international arbitration. In choice of law analyses, lex mercatoria addresses specific difficulties relating to the conflict of laws through a principled decision making, such as the applicable conflict rules, and the interpretation of the parties’ intentions as to the applicable substantive rules. In its substantive application, lex mercatoria deals with, either as lex contractus or as lex fori, the interpretation, supplementation and correction of the contract as well as the applicable national laws in accordance with the basic principles, on which the order of international commerce rests.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Commercial law; Conflict of laws; Foreign trade regulation; Law merchant

Arbitrage transnational et droit international général (2012) - Jacob, Patrick; Latty, Franck (Annuaire Français de Droit International, 2012)

La priorité chronologique reconnue à l'arbitre en droit maritime français, particularisme ou universalisme ? Le principe dit de compétence-compétence - Yildiz, Irfan (Aix-Marseille Université, 2012)
L’abandon progressif du contrôle de l’opposabilité de la clause d’arbitrage au destinataire par la juridiction étatique au profit de l’arbitre sur le fondement de l’aspect négatif du principe de compétence-compétence a donné lieu à de nombreux critiques. Certains auteurs l’ont approuvé, valorisant une application rigide de l’effet négatif du principe, tandis que d’autres l’ont critiqué solidement. Ainsi, il est légitimement permis de s’interroger sur les excès de l’effet négatif du principe de compétence-compétence et le bien-fondé de l’abandon du contrôle de l’opposabilité à l’arbitre par les juges étatiques. Pour ce faire, nous allons, dans un premier temps, examiner le droit accordé à l’arbitre d’être juge de sa propre compétence de manière prioritaire, plus précisément le principe de compétence-compétence (Chapitre I). Ensuite, nous allons nous interroger sur l’extension de la clause d’arbitrage au destinataire au regard du principe de compétence-compétence, qui est considéré de remettre en cause ce principe (Chapitre II).
Keywords: Arbitre droit maritime; Compétence-compétence; Transport maritime

Duty of Confidentiality: Myth or Reality? - Yu, Hong-Lin (Civil Justice Quarterly, 2012)
Explores the extent to which there is a duty of confidentiality in relation to the information used in arbitration proceedings. Considers how the duty is regulated by arbitration rules in different countries and whether there is a sufficient consensus to develop an internationally accepted principle of duty of confidentiality. Discusses which jurisdictions have an implied duty of confidentiality in the parties' arbitration agreement. Looks at how confidential information is defined in different jurisdictions, who is bound by the duty of confidentiality and the exceptions to the duty.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Confidential information; Confidentiality; Confidentialité; Information confidentielle